Using Predictive Storybooks to Foster Backward Counting: An Explanatory Sequential Study in Indonesian Kindergartens - Widayati, Sri; Simatupang, Nurhenti Dorlina; Wiryanto, Wiryanto; Siswono, Tatag Eko Yuli; Blazic, Milena Mileva (Jurnal Pendidikan Progresif, 2025)
Using Predictive Storybooks to Foster Backward Counting: An Explanatory Sequential Study in Indonesian Kindergartens. Objectives: This study aims to examine the effectiveness of the storybook "10 Bottles of Milk " as a learning medium for backward counting and to explore teachers' perceptions of its implementation. Methods: The study used a mixed-methods explanatory sequential design. Quantitatively, a pretest–posttest design was used with 150 kindergarten children from 10 institutions (A–J) in Surabaya, Indonesia, each comprising 15 children. The instrument, a backward counting test, was analyzed using the Wilcoxon Signed-Rank Test. Qualitatively, interviews were conducted with 10 prospective teachers who carried out storytelling activities using the "10 Bottles of Milk" ledger and analyzed using a theme, accompanied by a word cloud visualization (word cloud) to capture the dominant word concept. Findings: The quantitative results showed an increase of 2.66 points in the average score from the pretest to the posttest (p < 0.001), indicating that the storybook "10 Bottles of Milk " had a significant effect on children's backward counting ability. The qualitative results show that the storybook of 10 Bottles of Milk effectively makes children understand the concept of counting back from 10-1. The results of quantitative and qualitative research consistently confirm that the storybook "10 Bottles of Milk " is an effective learning medium for backward counting in early childhood. Conclusion: Overall, the combination of quantitative and qualitative results indicates that the storybook "10 Bottles of Milk" is an effective learning medium for stimulating backward counting skills in early childhood. The use of predictive books with attractive visuals encourages children's active involvement in storytelling activities and supports the development of early numeracy in kindergarten.Keywords: mixed method, explanatory sequential, backwards counting, early childhood.